The Effect Of Learning Simile On Essay Writing Skills For First Year Secondary School Students In Arab Schools/ Ø£Ø«Ø± Ø§Ù„ØªØ´Ø¨ÙŠÙ‡ ÙÙŠ ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© Ø§Ù„Ø¥Ù†Ø´Ø§Ø¦ÙŠØ© Ù„Ø¯Ù‰ Ø·Ù„Ø¨Ø© Ø§Ù„ØµÙ Ø§Ù„Ø£ÙˆÙ„ Ø§Ù„Ø«Ø§Ù†ÙˆÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Shittu, Abdulhakeem; Abdullahi, Lawal (Ijaz Arabi Journal of Arabic Learning, 2020)
This research titled: â€œEffect of Learning Simile on Essay Writing Skills of SSI Arabic Secondary Students in Kaduna State, Nigeria,â€ tried to unravel the subject matter. The research problem emanated from the weaknesses experienced by the researchers in the essay writing of the students in the course of their teaching at secondary levels. Thus, they formulated a research question with the aim of answering it through the usage of the experimental method. As such, they grouped their students into two: experimental and Control group, in which each of the groups consisted of ninety (90) students. The experimental group was taught simile using particular treatment, while the control group was taught conventionally. Consequently, it was vividly clear that those exposed to special treatment performed better than their counterpart in essay writing. Thus, the researchers recommend that: Teachers should give serious attention to the use of special treatment in the course of teaching rhetorics, as this would enhance their performance in writing skills. The National Board for Arabic and Islamic Studies (NBAIS) was also advised to consider what will improve the teaching/learning of rhetorics in the course of their curriculum development and implementation.